Managing Modern Healthcare Knowledge, Networks and Practice - Bresnen, Michael (Taylor & Francis, 2017)
Managing Modern Healthcare seeks to draw a number of important and grounded lessons about how management networks develop and influence the spread of management knowledge and practice; how management training and development relates to the needs of managers facing challenging conditions; and how those conditions are shaping the nature of healthcare management.